Gelation of Ionic Liquids with Silica Nanoparticles: The Role of Cation Structure and Interactions. - Leandro, Esteban Rucavado (My University, 2011)
This project investigates the gelation of ionic liquids using silica nanoparticles. The overall aim is to learn more about the ion-ion and ion-silica interactions in ionic liquid-silica dispersions and gels. Differences in the interactions between ionic liquid and silica are introduced by changing the structure of the cations. Four different ionic liquid based on imidazolium cation and [TFSI] anion have been used to gel silica nanoparticles. The structure of the cations is varied by changing the length and the end-group on the alkyl chain of the imidazolium ring, introducing e.g. the possibility of hydrogen bonding. Each ionic liquid was found to have a different gel concentration, 3.8wt% for [C2MIM][TFSI], 4wt% for [EtOHMIM][TFSI], 3.5wt% for [C5MIM][TFIS], and 3.6wt% for [SMIM][TFSI]. At the gel concentration all samples were weak gels, showing a yield stress behaviour. Below 4wt% phase separation was observed for the [EtOHMIM][TFSI] silica dispersions. The gelation of the dispersions does not have any dramatic influence on the properties of the ionic liquid. The glass transition temperature does not change and the conductivity decreases only slightly. Raman spectroscopy shows that there are no changes on the strong Raman band at 740 cm⁻¹ (expantion-contraction of the entire [TFSI] anion) with silica concentration. From the results obtained, it is possible to conclude that in the gel, the silica matrix acts as a “container” for the ionic liquid: immobilizing the ionic liquid without making important changes to the properties.
Keywords: Fysik; Physical Sciences